ISOLASI DAN KARAKTERISASI METABOLIT SEKUNDER DARI EKSTRAK ASETON DAUN MACARANGA PRUINOSA BANGKA BELITUNG - Roanisca, Occa; Syah, Yana M. (Jurnal Riset Kimia, 2016)
Macaranga is a large genus in Euphorbiaceae, locally known as "Mahang-mahangan", and consisting about 300 species. Distribution of Macaranga is widespread from Africa and Madagascar in the west to the tropical regions of Asia including Indonesia. Based on previous research of the M. pruinosa, secondary metabolites that have been reported are flavonoid, and stilbenoid derivatives from Borneo. M. pruinosa that grow in South Sumatra produce poilanoat acid (diterpene). Therefore, this research is done to investigate phytochemical constituent of leaves of M. pruinosa from Bangka Belitung Islands. Isolation is done by maceration in acetone, separation and purification using vacuum liquid chromatography and radial chromatography. Structure determination were elucidated by 1H-NMR,13C-NMR, 2D NMR. Two compounds are identified as flavanon derivatives. They are nymphaeol B, and 6-farnesil-3',4',5,7-tetrahidroksiflavanon. These compounds are substituted with terphenyl group, known as geranyl (C10), and farnesyl (C15). Nymphaeol B (1) and compound of 6-farnesil-3', 4', 5,7-tetrahidroksiflavanon (2) have been found in other species of Macaranga. In conclusion, we here acquired two phenolic derivatives substituted by terphenyl groups from acetone extracts of leaves of M. pruinosa from Bangka Belitung. They are nymphaeol B, and 6-farnesil-3',4',5,7-tetrahidroksiflavanon. The result showed that M.pruinosa can produce different secondary metabolites depend on where they grow.Â